2021
DOI: 10.1093/jncics/pkab078
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Breast Cancer Risk in Men: A National Case-Control Study in England and Wales

Abstract: Background Breast cancer is rare in men, and information on its causes is very limited, from studies that have generally been small. Adult obesity has been shown as a risk factor but more detailed anthropometric relations have not been investigated. Methods We conducted an interview population-based case-control study of breast cancer in men in England and Wales including 1,998 cases incident during 2005–2017 at ages under 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…The pooling project reported a 19% increased risk per 5-unit increase in BMI (OR = 1.19, 95% CI = 1.1 to 1.3) and a 35% statistically significantly increased risk for obese men (BMI ≥ 30 kg/m 2 ) compared with normal weight men (BMI = 18.5-24.9 kg/m 2 ) ( 4 ). Generally consistent with this information, Swerdlow et al ( 10 ) found that recent waist-to-height ratio was a stronger risk factor than that at age 20 years.…”
supporting
confidence: 52%
See 4 more Smart Citations
“…The pooling project reported a 19% increased risk per 5-unit increase in BMI (OR = 1.19, 95% CI = 1.1 to 1.3) and a 35% statistically significantly increased risk for obese men (BMI ≥ 30 kg/m 2 ) compared with normal weight men (BMI = 18.5-24.9 kg/m 2 ) ( 4 ). Generally consistent with this information, Swerdlow et al ( 10 ) found that recent waist-to-height ratio was a stronger risk factor than that at age 20 years.…”
supporting
confidence: 52%
“…In summary, findings from the study by Swerdlow and colleagues ( 10 ) provide additional evidence of the detrimental role of obesity and central obesity on breast cancer risk and warrant further studies. Ideally, future research efforts examining the association of obesity and male breast cancer should use a prospective design; include a diverse population of men, particularly Black men, and sufficient sample size to classify men according to clinically meaningful BMI categories; evaluate risk by tumor subtypes; and conduct anthropometric measurements to be able to characterize body fat distribution and body composition.…”
mentioning
confidence: 80%
See 3 more Smart Citations